Fundamental origin of the large impact of strain on superconducting Nb3Sn. (7th September 2018) - Godeke, A; Hellman, F; Kate, H H J ten; Mentink, M G T
Abstract: Superconductors can carry very high current densities without resistive loss. This makes them highly suitable for the construction of compact high field magnets of several tens of tesla. However, with increasing current density and magnetic field come high Lorentz loads and high strain levels, and it is empirically known that superconducting properties are affected by strain. The superconducting properties of the most commonly used high field material, Nb3 Sn, are particularly badly affected by strain. Here we demonstrate that strain causes significant sub-lattice distortion in the A15 lattice structure of Nb3 Sn, and show how this leads to the relatively large reduction of its superconducting properties. The changes are found to be primarily due to changes in the electron density of states, with a lesser contribution due to changes in the phonon spectrum. The amount of sub-lattice distortion further depends on crystal orientation. These findings suggest that it is possible to mitigate the reduction of the current carrying capacity by strain through crystal alignment and sub-lattice stabilization. This would enable superconducting magnets to reach a significantly higher magnetic field, and ease their construction by simplifying react-and-wind coil fabrication.